Investigation of pyrethroid resistance mutations in Linognathus stenopsis lice collected from goats in western and northwestern Iran - Seydi-Gazafi, Khadijeh; Tavassoli, Mousa; Mardani, Karim (Frontiers in Veterinary Science, 2024)
Introduction Linognathus stenopsis lice are an extensive parasitic concern in goat populations worldwide, posing significant economic and health risks. This study examined the identification of alleles of resistance to pyrethroid and mutations in L. stenopsis samples obtained from goats in five provinces in western and northwestern Iran. Methods Morphological and molecular techniques were employed to identify the louse species. Molecular identification methods and gene sequencing were used to identify resistance-associated mutations in the voltage-gated sodium channel (VGSC) gene. Results and discussion The results revealed that six amino acid substitutions, including threonine-to-isoleucine (T917I), leucine-to-phenylalanine (L920F), isoleucine-to-phenylalanine (I927F), phenylalanine-to-alanine (F928A), valine-to-arginine (V929R), and arginine-to-leucine (R930L) mutations, were present in the VGSC gene of L. stenopsis lice from various regions of Iran. These findings suggest the potential for pyrethroid resistance development in this louse species, highlighting the importance of integrated pest management (IPM) strategies. Such strategies, which combine selective insecticides, regular grooming, and environmental sanitation, are crucial for effectively managing L. stenopsis infestations and preserving the efficacy of pyrethroids for pest control. Moreover, the emergence of novel kdr mutations underscores the need for ongoing research into the molecular mechanisms underlying these mutations. This research is vital for developing strategies to combat pyrethroid resistance and maintaining the efficacy of insecticides in controlling lice.